Effectiveness of Differentiation Learning Strategies in Mathematics Learning at Junior High School - Sinta Dameria Simanjuntak; Romega Tinambunan; Imelda Imelda; Ribka Kairani Sembiring; Israil Sitepu (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This study aimed to determine whether differentiation learning in junior high school mathematics learning was practical. The method used in this study is a quasi-experimental research design with Pretest-Posttest Control Group Design. The population in this study were all eighth graders of St Yoseph Private Junior High School Medan, which consisted of five classes with 32 people in each class. The sample in this study was 64 students consisting of 32 students for the experimental class and 32 for the control class. The results showed that the average student activity in content differentiation was 2.33 in the excellent category, the application of process differentiation was 2.33 in the excellent category, and the application of product differentiation was in a suitable category. The average value of teachers' ability to implement content differentiation is 3 in the excellent category, the average value in the implementation of process differentiation is 2.25 in the excellent category, and the implementation of product differentiation is 2.75 in the excellent category. Based on the results of research and hypothesis testing that has been carried out, the differentiation learning process runs effectively, which can improve students' mathematical abilities. This can be seen from the difference in the average post-test score of students in the experimental class and control class of 2.25%, the percentage of students who meet the KKM is 62.5%, the average student activity is 76.6%, and also the average level of teacher ability in managing differentiation learning in the experimental class is 89%. This research implies that differentiation learning is effectively used for junior high school mathematics learning